麻管局 关于国际管制药物供应情况的 2022年年度报告补编 - International Narcotics Control Board (United Nations, 2023)
The International Narcotics Control Board (INCB) issued supplementary reports on the availability of controlled substances for medical purposes in 1989, 1995, 2010, 2015 and 2018. In 2022, INCB has collected and analysed information from Member States and civil society to once again provide the international community with an update on the situation and to recommend remedial action. The data confirm the persistent disparities between regions in the consumption of opioid analgesics for the treatment of pain. Almost all such consumption is concentrated in Western Europe, North America, Australia and New Zealand. Consumption levels in other regions are often not sufficient to meet the medical needs of the population. These regional imbalances are not due to a shortage of opiate raw materials. Supply has been found to be more than sufficient to satisfy the demand reported to INCB by Governments, but it is evident that a large number of countries may not be accurately reflecting the actual medical needs of their populations in their reported demand, and hence the disparity in availability.